UPAYA MENINGKATKAN KEMAMPUAN PRAKTIK SHALAT SISWA MELALUI PEMANFAATAN MEDIA AUDIO VISUAL DI KELAS III SD NEGERI LAWE SEKERAH KABUPATEN ACEH TENGGARA - Cut Rivani; Nurbayani Ali (UIN Sumatera Utara Medan, 2025)
Negeri Lawe Sekerah, Aceh Tenggara, in performing the practice of Islamic prayer. This issue highlights the need for innovative learning approaches that address students’ visual and procedural learning needs. The objective of this study was to improve students’ prayer practice skills through the use of audio-visual media. This research employed a classroom action research design based on the Kemmis & Taggart model, which included two cycles with four phases: planning, acting, observing, and reflecting. Data were collected through observation sheets and documentation. The findings showed a significant improvement in students’ abilities, with the average score increasing from 63.7 in the pre-action stage to 73.19 in Cycle I, and further to 85.01 in Cycle II. These results confirm that the integration of audio-visual media effectively enhances students' performance in both the movements and recitations of prayer. It can be concluded that audio-visual media serve as a pedagogically relevant and empirically proven solution to improve the quality of Islamic religious learning, particularly in practical prayer instruction at the elementary school level.